2017
DOI: 10.1590/s0100-736x2017001200004
|View full text |Cite
|
Sign up to set email alerts
|

False-negative reactions to the comparative intradermal tuberculin test for bovine tuberculosis

Abstract: According to the Brazilian National Program for the Control and Eradication of Animal Brucellosis and Tuberculosis (PNCEBT), the routine tests for the diagnosis of bovine tuberculosis in the country are the simple intradermal tuberculin test (SITT) of the Ministry of Agriculture, Livestock and Food Supply (MAPA), the caudal fold test and the comparative intradermal tuberculin test (CITT). The latter is also used as a confirmatory test. A group of 53 animals from three dairy herds in a focal area for bovine tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Therefore, in regions with high bTB prevalence and no indemnity for cattle owners, such as from this study, seems to not be reasonable in the adoption of the above procedure since it notably would increase the false positive animals leading to unjusti able economical loss and ultimately low adherence or even avoidance to eradication programs. On the other hand, the parallel strategy CCT + ELISA, would result in an increase on the proportion of herds infected by 60% and at animal level the increase of positive animals by 5.5%, these results are compatible with previous studies (17,25,36). Thus, the parallel interpretation of the diagnostic techniques that detect cellular and humoral immune response although can be recommended as supplemental test to detect false negative TST animals (17,25,33,34,36) should be considered according the local circumstances.…”
Section: Prevalence Of Tuberculin Skin Test X Elisa For the Diagnosissupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, in regions with high bTB prevalence and no indemnity for cattle owners, such as from this study, seems to not be reasonable in the adoption of the above procedure since it notably would increase the false positive animals leading to unjusti able economical loss and ultimately low adherence or even avoidance to eradication programs. On the other hand, the parallel strategy CCT + ELISA, would result in an increase on the proportion of herds infected by 60% and at animal level the increase of positive animals by 5.5%, these results are compatible with previous studies (17,25,36). Thus, the parallel interpretation of the diagnostic techniques that detect cellular and humoral immune response although can be recommended as supplemental test to detect false negative TST animals (17,25,33,34,36) should be considered according the local circumstances.…”
Section: Prevalence Of Tuberculin Skin Test X Elisa For the Diagnosissupporting
confidence: 82%
“…TST results is being reported and suggests that their application to test non-infected herds would help to increase the performance of the screening strategy in current bTB eradication programs (19,25,36).…”
Section: Prevalence Of Tuberculin Skin Test X Elisa For the Diagnosismentioning
confidence: 99%
“…In view of that if the true prevalence is the same than the observed on TST screenings, we would expect a lower prevalence than in the previous studies. Considering the sensitivity of 28.2% and specificity of 57.1% found in a controlled field study (43), the practice of TST as a screening test for BTB in Amazonas can result in a worrisome number of false-negative animals remaining in herds. The absence of compensatory measures on the PNCEBT, is a factor to be considered as a hamper for the producers' adherence to the program, successful countries on BTB eradication adopted the screening and elimination police as well as compensatory measures to incentivize animal owners within the programs (5).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in a study conducted in 2015 in RS, the Comparative Cervical Test revealed 26.4% of reactors and 13.2% of inconclusive animals in 53 dairy cattle premises. At slaughter, TB-like lesions were found in tissues of 92.9% and 71.4% of the reactor and inconclusive animals [ 61 ], indicating that the use of TLL can be a good proxy of the infected animals in this region. However, an important limitation of the official veterinary system is the absence of routine confirmation of these TLL reported in slaughterhouses.…”
Section: Discussionmentioning
confidence: 99%